Performance of PFA-Cement-Sand stabilized column in soft soil / Mohamad Shakri Mohmad Shariff - Mohmad Shariff, Mohamad Shakri (2017)
Renewable and eco-friendly development are vital concepts to be considered for ground improvement methods in construction practices. One of the method to achieve this is by implementing usage of waste material in construction. Therefore, the main objective of this research is to use Pulverized Fuel Ash (PFA) in stabilized column by studying the impact of this waste material against strength parameters of the stabilized column. small shear box (SSB) and big shear box (BSB) tests were conducted to determine shear strength parameters while unconfined compression test (UCT) are carried out to determine unconfined compressive strength (q ).